A SMALL WASTEWATER TREATMENT STATION BUILT WITH PVC AND ASSOCIATED TO BIOGAS POWER GENERATOR - Lamas, W. Q.; Silveira, J. L.; Giacaglia, G. E. O. (Revista de Engenharia Térmica, 2008)
This work describes features related to a small wastewater treatment station installed at Sao Paulo State University, Faculty of Engineering, and Campus of Guaratingueta. An introduction about this topic is discussed focusing on its importance for environment (greenhouse effect) and for sewage treatment. Several works related to this topic are discussed. Following, a general plant is described. Concluding, some articular aspects are discussed such as CDO and BDO removal. Also, a comparison between real measured values and values recommend by Brazilian environmental legislation is discussed.